2022
DOI: 10.3389/fpubh.2022.987526
|View full text |Cite
|
Sign up to set email alerts
|

Association between social support and medication literacy in older adults with hypertension

Abstract: BackgroundReduced physical function and reduced social networks place older adults with hypertension at high risk for medication-related harm. Medication literacy is one of the preventable factors that affect the success of drug therapy for hypertension. However, little is known about the level of medication literacy and its influencing factors in older adults with hypertension.ObjectiveThe purpose of this study was to investigate the levels of social support and medication literacy, and the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…This study found a positive correlation (0.449, Frontiers in Pharmacology frontiersin.org p < 0.01) between social support and medication literacy. This is aligned with the results of Shen Z et al, which highlighted the important role of social support in promoting medication literacy in older adult patients with hypertension (Shen et al, 2022). In the SEM, the effect coefficient of social support on medication literacy was 0.40, implying the importance of boosting social support to improve older adult patients with hypertension.…”
Section: Analysis Of the Influence Of Social Support On Medication Li...supporting
confidence: 88%
“…This study found a positive correlation (0.449, Frontiers in Pharmacology frontiersin.org p < 0.01) between social support and medication literacy. This is aligned with the results of Shen Z et al, which highlighted the important role of social support in promoting medication literacy in older adult patients with hypertension (Shen et al, 2022). In the SEM, the effect coefficient of social support on medication literacy was 0.40, implying the importance of boosting social support to improve older adult patients with hypertension.…”
Section: Analysis Of the Influence Of Social Support On Medication Li...supporting
confidence: 88%
“…We also used SEM to examine whether the associations among these factors are mediated by health literacy and/or social support in patients with hypertension. Figure 1 outlines the hypotheses we proposed according to previous studies [ 9 11 , 13 , 18 , 19 ]. We hope that the model will reveal relationships between the tested factors and medication adherence that will be helpful for developing effective measures to improve medication adherence among patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…This support includes help from family, friends, and medical institutions. Research indicates that support from family and friends encourages patients to persist in physical activities, while medical institutions enhance physical literacy by offering necessary opportunities, resources, and support [ 15 ]. Engaging in social networks, communicating with others, and sharing experiences in managing hypertension not only provide motivation and positive feedback but also promote patients’ engagement in beneficial physical activities.…”
Section: Introductionmentioning
confidence: 99%